복잡계 과학 방법론을 활용한 한의학 연구: 현황과 전망 - 장동엽(Dongyeop Jang); 조나현(Na-Hyun Cho); 이기은(Ki-Eun Lee); 권영규(Young-Kyu Kwon); 김창업(Chang-Eop Kim) (동의생리병리학회지, 2021)
Traditional Korean medicine (TKM) takes a holistic view that emphasizes the balance between the elements constituting the human body or between the human body and the external environment. To investigate the holistic properties of TKM, here we propose to apply the methodology of complexity science to the TKM research. Complexity science is a discipline for studying complex systems with interactions between components that raise the behaviour as a whole which can be more than the sum of their parts. We first provide an introduction to the complexity science and its research methods, particularly focusing on network science and data science approaches. Next, we briefly present the current status of TKM research employing these methods. Finally, we provide suggestions for future research elucidating the underlying mechanism of TKM, both in terms of biomedicine and humanities.